Respuesta :

Answer:

x=34/5 y=6/5

Step-by-step explanation:

so first you need to isolate one variable in one equation

so lets use 3x-12y=6

3x=12y+6

x=4y+2

then, as the name implies, we substitute it into the second equation

3(4y+2)-7y=12

then we simplify

12y+6-7y=12

5y=6

y=6/5

then we plug it in to find x

3x-7(6/5)=12

3x-42/5=12

3x=102/5

x=34/5

check work

3(34/5)-12(6/5)=6

102/5-72/5=6

30/5=6

6=6

Answer:

x=6.8 y=1.2

Step-by-step explanation:

Finding equation for x

3x-12y=6

3x-12y+12y=6+12y

3x=6+12y

3x÷3=(6÷3)+(12y÷3)

x=2+4y

plug x into the equation

3(2+4y)-7y=12

6+12y-7y=12

6+5y=12

6+5y-6=12-6

5y=6

5y÷5=6÷5

y=1.2

finding x

3x-12(1.2)=6

3x-14.4=6

3x-14.4+14.4=6+14.4

3x=20.4

x=6.8

check

3(6.8)-12(1.2)=6

20.4-14.4=6